Loss of AP-2delta reduces retinal ganglion cell numbers and axonal projections to the superior colliculus. Issue 1 (December 2016) - Li, Xiaodong; Gaillard, Frédéric; Monckton, Elizabeth; Glubrecht, Darryl; Persad, Amit; Moser, Markus; Sauvé, Yves; Godbout, Roseline
Abstract Background AP-2δ is the most divergent member of the Activating Protein-2 (TFAP2) family of transcription factors. AP-2δ is restricted to specific regions of the CNS, including a subset of ganglion cells in the retina. Retinal ganglion cells (RGCs), the only output neurons of the retina, are responsible for transmitting the visual signal to the brain. Results AP-2δ knockout results in loss ofBrn3c (Pou4f3 ) expression in AP-2δ -positive RGCs. WhileAP-2δ-/- mice have morphologically normal retinas at birth, there is a significant reduction in retinal ganglion cell numbers by P21, after eye opening. Chromatin immunoprecipitation indicates thatBrn3c is a target of AP-2δ in the retina. Using fluorochrome-conjugated cholera toxin subunit B to trace ganglion cell axons from the eye to the major visual pathways in the brain, we found 87 % and 32 % decreases in ipsilateral and contralateral projections, respectively, to the superior colliculus inAP-2δ-/- mice. In agreement with anatomical data, visually evoked responses recorded from the brain confirmed that retinal outputs to the brain are compromised. Conclusions AP-2δ is important for the maintenance of ganglion cell numbers in the retina. Loss of AP-2δ alters retinal axonal projections to visual centers of the brain, with ipsilaterial projections to the superior colliculus being the most dramatically affected. Our results have important implications for integration of the visual signal at the superior colliculus.